Tau degradation in Alzheimer's disease: Mechanisms and therapeutic opportunities - Wang L.; Sooram B.; Kumar R.; Schedin-Weiss S.; Tjernberg L.O.; Winblad B. (My University, 2025)
In Alzheimer's disease (AD), tau undergoes abnormal post-translational modifications and aggregations. Impaired intracellular degradation pathways further exacerbate the accumulation of pathological tau. A new strategy – targeted protein degradation – recently emerged as a modality in drug discovery where bifunctional molecules bring the target protein close to the degradation machinery to promote clearance. Since 2016, this strategy has been applied to tau pathologies and attracted broad interest in academia and the pharmaceutical industry. However, a systematic review of recent studies on tau degradation mechanisms is lacking. Here we review tau degradation mechanisms (the ubiquitin–proteasome system and the autophagy–lysosome pathway), their dysfunction in AD, and tau-targeted degraders, such as proteolysis-targeting chimeras and autophagy-targeting chimeras. We emphasize the need for a continuous exploration of tau degradation mechanisms and provide a future perspective for developing tau-targeted degraders, encouraging researchers to work on new treatment options for AD patients. Highlights: Post-translational modifications, aggregation, and mutations affect tau degradation. A vicious circle exists between impaired degradation pathways and tau pathologies. Ubiquitin plays an important role in complex degradation pathways. Tau-targeted degraders provide promising strategies for novel AD treatment. © 2025 The Author(s). Alzheimer's & Dementia published by Wiley Periodicals LLC on behalf of Alzheimer's Association.